The future is CLEAR: Community-Led Engagement for Adaptability & Resilience - Stewart, Helen (The International Hydrographic Review, 2025)
Climate change poses an existential threat to communities living on the water’s edge. It is possible to design climate adaptation and climate resilience policies that safeguard communities and support sustainable living, but implementing such policies is difficult without understanding the needs and cultural practices of the people living there. Community-Led Engagement for Adaptation and Resilience is a way to bring community members into policy and planning stages of adaptation and resilience efforts. This Keynote discusses different types of community-led engagement that the International Hydrographic Organization (IHO) practices to support its member states, how it can improve its own policies, and how the IHO and member states can collaborate to support their needs and those of people who are at greatest risk of climate change-related hazards.